SEWAGE TREATMENT SYSTEM (2019)
Provided is a sewage treatment system capable of maintaining a positive dissolved oxygen concentration of sewage flowing down through a sewer conduit downstream of a relay pump station, and changing a microbial state on an inner wall of the sewer conduit to prevent corrosion of the sewer conduit. The sewage treatment system comprises: dehydration means connected to an initial sedimentation pond and/or a final sedimentation pond of a sewage treatment facility and configured to receive surplus sludge from the initial sedimentation pond and/or return sludge from the final sedimentation pond and dehydrate the received surplus sludge and/or the received return sludge; a microbial material production device configured to supply oxygen to the dehydrated sludge received from the dehydration means while maintaining a temperature of the dehydrated sludge within the range of 60° C. to 110° C., to subject the dehydrated sludge to aerobic fermentation using Gram-positive aerobic microbes in the hydrated sludge, thereby producing a microbial material in which Gram-negative anaerobic and facultative anaerobic microbes in the hydrated sludge are decomposed and extinguished and which contains aerobic microbial spores produced after the aerobic fermentation; water feeding means configured to feed water from any part of the sewage treatment system to the after-mentioned microbe activation device; a microbe activation device configured to receive the microbial material from the microbial material production device, and supply the water from the water feeding means to the received microbial material, while maintaining a temperature and an oxygen concentration of the water, respectively, within the range of 10° C. to 40° C., and within the range of 1 to 10 mg/L, thereby germinating the spores of the microbial material to activate the microbial material; and oxygen supply means configured to supply oxygen to the sewage at any position of the relay pump station; wherein the sewage including the activated microbial material and the oxygen supplied from the oxygen supply means is sent from the relay pimp station to the sewage treatment facility.